Applications for mobile devices: support for fashion collection development (ModaPalavra e-periódico, 2015)
The development of collections or products is part of the activities of a fashion student, being this practice part of their profession. Traditionally, the practices related to the creation of fashion were performed manually, but with the emergence of specific software they started to be made on the computer and recently on mobile devices. This study proposes an exploratory research in order to identify applications on the IOS platform, which can be used during some stages of the collection development, both in academic and professional circles. As a result, it is recommended applications to the stages of research, theme collection, color palette and drawing: Paper by FiftyThree, Bamboo Paper, Moodboard, myPANTONE and Prêt-à-Template.
Keywords: fashion; collection development; applications dor tablets